ROLE OF PROBIOTICS AND PREBIOTICS IN PREVENTION AND TREATMENT OF DISEASES IN CHILDREN: AN EVIDENCE BASED CRITICAL ANALYSIS - BANDYA SAHOO, (International Journal of Pharma and Bio Sciences, 2015)
Probiotics are commonly used in pediatric office practice. The purpose of this clinical report is to review uses of probiotics and prebiotics in children and summarize what is currently known about their health benefits supported by evidence-based medicine. The guidance in this report will help paediatricians to make appropriate decisions regarding which prebiotic and probiotic to use in a particular disease and at what dose. Probiotics are beneficial for treating some diseases such as acute rota viral diarrhoea, antibiotic associated diarrhoea and preventing Necrotizing Enterocolitis. There might also be a beneficial effect in patients with colic and Irritable Bowel Syndrome. The role of probiotics remains unproven in preventing or treating atopic diseases. Caution should be exercised in giving probiotics to patients with immunodeficiency. The efficacy of probiotics is both strain, disease and dose-specific.